The Effect of GCG and Leverage on Financial Performance: Evidence from Construction Firms - Aldo, Sultan; As'ari, Hasim (SAN Scientific, 2023)
This study aims to investigate the impact of GCG (Governance Code Guidelines) and leverage on the financial performance of construction and building firms listed on the Indonesia Stock Exchange between 2018 and 2021. The research involved 22 firms in the building construction sector, and data collection utilized a purposive sampling method to examine eight selected firms. The analysis method employed was Multiple Linear Regression. The findings indicate that the Independent Board of Commissioners has no significant effect on financial performance, whereas GCG (Board of Directors) negatively influences Financial Performance. Additionally, Leverage (DER and DAR) impacts Financial Performance. Firm management can use GCG and leverage as strategic tools to enhance financial performance and communicate this information to the market. Firms implementing good corporate governance and showcasing concern for the environment can receive incentives or reputation benefits from the community, which can further improve their financial performance